Effect of Strenuous Physical Activity on Cortisol and Leukocyte in Mice - Mushidah, Mushidah; Nasihun, Taufiqurrahman; Hussaana, Atina (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2016)
Introduction: Strenuous physical activities cause an increase in free radicals, physical stress, psychological stress and decreased immunity. Psychological stress affects the hypothalamic-pituitary-adrenal (HPA) axis leading to increased levels of cortisol and blood cell apoptosis. However, the studies on the effect of strenuous physical activities on cortisol levels and leukocyte count showed inconsistent findings. Objectives: To examine the effect of strenuous exercise on cortisol levels and leukocytes count.Methods: In this study with post test only control group design, 15 male BALB/c mice were randomly assinged to the following 3 groups: control (non-exercised) group (G-0), once strenouse physical activity (G-1), 3 times strenuous physical activity (G-2). Cortisol levels were evaluated by ELISA.White blood count was determined. Data were analyzed by one way ANOVA test followed by Post Hoc and Pearson, with a confidence level of 95%.Results: The mean cortisol level in group G-0, G-1, G-2 were 11.86 ± 2.10μg/dL, 32.00 ± 0.86μg/dL, 44.58 ± 1.74μg/dL respectively. The number of leukocytes in G-0, G-1, G-2 were 6180±540.37/mm3, 4650±217.94/mm3, 4180±130.38/mm3 respectively. One way ANOVA showed a significant difference between groups (p <0.001). Post Hoc Test showed that the levels cortisol in G-1 and G-2 were significantly higher than thatof G-0 (p <0.001). The number of leukocyte in G-1 and G-2 was lower than that of G-0 (p <0.001). There was a significant negative correlation between cortisol levels and the number of leukocytes (r = -20.14, p <0.001).Conclusions: Strenuous physical activity increasescortisol levels and decrease the number of leukocytes in BALB /c mice.